Nutrient availability in acidic soil added with composted paddy husk amendment - Simol, Carlina Freddie; Chubo, John Keen; Jie, Patricia Hung King; Kian, Huat Ong; Chew, Cindy; Simol, Ira Carlbrenie; Nawi, Khalid (Penerbit Universiti Kebangsaan Malaysia, 2021)
Organic amendments such as composted paddy husk can improve the fertility of tropical acid soil through replenishment of cations, reduction of phosphorus and potassium fixation, increase soil total carbon and nutrients availability. The objective of this study was to determine the effect of incubation period on soil quality and availability of major nutrients in composted paddy husk treated using different ligninolytic microbes isolated from termite guts. Each treatment of soil with various compost mixtures was incubated for 30, 60, and 90 days before harvested. The physico-chemical properties of the incubated soils were determined using standard procedures. Results indicated that soil pH, electrical conductivity, total nitrogen and phosphorus, available phosphorus, exchangeable potassium, magnesium, and calcium interacted positively to incubation time and treatments. Thus, the application of composted paddy husk improved soil carbon content, reduced soil acidity, and increased the availability of essential plant nutrients.